Association between osteoprotegerin gene polymorphisms and cardiovascular disease in type 2 diabetic patients - Guo,Changlei (2013)
Osteoprotegerin (OPG) gene polymorphisms (T245G, T950C and G1181C) have been associated with osteoporosis and early predictors of cardiovascular disease. The aim of this study was to evaluate whether these polymorphisms contribute to cardiovascular disease (CVD) in type 2 diabetic patients. We performed a case-control study with 178 CVD subjects with diabetes and 312 diabetic patients without CVD to assess the impact of variants of the OPG gene on the risk of CVD. The OPG gene polymorphisms were analyzed by using the polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP). There was no significant association between the T245G and G1181C polymorphisms and CVD in the additive genetic model (OR = 0.96, 95% CI 0.64-1.45, p = 0.79; OR = 1.06, 95% CI 0.81-1.39, p = 0.65, respectively). However, the C allele of the T950C polymorphism was independently associated with a risk of CVD in type 2 diabetic patients in this genetic model (OR = 1.38, 95% CI 1.07-1.80, p = 0.01). This study provides evidence that the C allele of the T950C polymorphism is associated with increased risk of CVD in diabetic patients. However, well-designed prospective studies with a larger sample size are needed to validate these results.